2008
DOI: 10.1016/j.acvd.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of ischaemia-modified albumin in patients with non-ST-segment elevation acute coronary syndromes

Abstract: Baseline levels of IMA were associated with both short- and long-term cardiovascular (CV) events in patients admitted for NSTE ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Blood sampling was processed as described using laboratory‐prepared tubes containing 3 ml of cold‐stop solution composed of inhibitors of degradation and red blood cell uptake of adenosine [36,39,41]. Samples were then maintained on ice until centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…Blood sampling was processed as described using laboratory‐prepared tubes containing 3 ml of cold‐stop solution composed of inhibitors of degradation and red blood cell uptake of adenosine [36,39,41]. Samples were then maintained on ice until centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…The groups that participate in this binding have been shown to be the α-amino group, the two intervening peptide nitrogen atoms, the δ-imidazole nitrogen from His3 and the side-chain carboxyl group of Asp1 [8]. In the presence of ischemia, structural changes take place in the N-terminus of albumin that rapidly reduce its binding capacity for transition metal ions, Co 2+ and Ni 2+ [9,10]. IMA is a marker formed after damage in the N-terminal region of albumin.…”
Section: Structure Of Imamentioning
confidence: 98%
“…Bali et al [9] demonstrated that the independent prognostic value of IMA was greater than that of conventional markers such as Tn-I and C-reactive protein for non-STsegment elevation (NSTE) ACS patients. The small sample size was mentioned as being a limitation of the study (n = 79).…”
Section: Use Of Ima In Acsmentioning
confidence: 98%
See 2 more Smart Citations